Participation factors in a self-quantification program for family caregivers of community-dwelling older adults with long-term care in Japan - Tomoko Wakui; Satoko Fujihara; Yoko Moriyama; Takeshi Nakagawa; Suguru Okubo; Shuichi Obuchi; Shuichi Awata; Ichiro Kai (BMC Research Notes)
Abstract Objective This study aimed to examine the characteristics of participation in the self-quantification program for family caregivers (CGs) who provide long-term care to community-dwelling older adults. The family CGs, allocated based on the percentage of the nation’s older population who needed care and met the inclusion criteria, who provided caregiving at least once a week for those aged 65 + and who were certified as needing care under the Japanese long-term care insurance program, were collected through online monitors. We compared the characteristics of the program participants and nonparticipants using logistic regression. Results A total of 2653 family CGs, including 195 study participants who engaged in self-quantification over 60 days and 2,458 nonparticipants who did not engage in self-quantification, were included in the analysis, with complete data available for all variables of interest. The survey included program participants who were predominantly male (55.9%), with an average age of 54.8 years (SD = 10.2). Participants tended to be fully employed (OR = 1.8; p < 0.01), but they were likely to experience greater burdens (OR = 1.8; p < 0.01) and daily caregiving demands (OR = 1.01; p < 0.01). This research highlights the potential efficacy of self-quantification programs for extensively burdened family CGs, illustrating that the requisites for support vary in accordance with the distinct characteristics of these CGs.